HUBUNGAN ANTARA KEPRIBADIAN DAN PENGEMBANGAN KARIER TENAGA PENDIDIK DENGAN KUALITAS PELAYANAN SEKOLAH DI LINGKUNGAN YAYASAN AS-SHOFA - Rysa Maulina; Azhar Azhar; Rr. SriKartikowati (Jurnal JUMPED (Jurnal Manajemen Pendidikan), 2017)
The aim of the study is to know the correlation between personality and careerdevelopment educators with service quality in the school as-shofa foundation. The source ofdata in this study is 112 teachers in as-shofa fuoundation who were selected using randomsampling technique. Data was analyzed that using correlation analysis. The result of this researchindicate that positive relationship between personality with service quality. The correlationcoefficient is 0,47 or positive relationship. The correlation career development with servicequality is 0,66. While relationship between personality and career development with servicequality is 0,71. The conclusion from correlation personality (X1) and career development (X2)with service quality (Y) is owning direction positive.